Comissões não remuneradas no IFSP Sertãozinho: participação dos servidores técnicos administrativos - Souza, Maria Eduarda de (2019)
This paper aimed to analyze how the dynamic of the cooperation of the administrative technical servers from the Sertãozinho campus of the Federal Institute of São Paulo (IFSP) works in relation to their participation in unpaid commissions. The research was developed from the assumptions of altruism, selfishness and cooperation, since monetary issues or other incentives are unrelated. In contrast to what may happens in private institutions, in this particular case, the attendees were mostly volunteers, and end up watching their workload increase. The present work used the motivational theories to cover the theme, but the game theory was chosen as the analysis factor to carry out the research. Game uses mathematical data and economic dynamics to deal with psychological and social factors. This kind of research approach is very interesting because, in a simpler way, it can capture the "cleanest" reactions of the target audience. The work was carried out with the administrative technical servers of the Sertãozinho campus, in three stages: quantitative survey regarding the participation of each server in commissions, virtual questionnaire, and face-to-face dynamics. In all moments of the work, considering the employees collaboration in the participation of each research stage, it was possible to observe the group cooperation subject. The results analyzed provided information that may be of great importance to afford the managers with data that may influence the motivation for the participation, and also the quality of the employees in these work groups. Keywords: Cooperation. Altruism. Motivation. Theory of games.